Accountability: Implications of the Effect of Understanding Government Accounting Standards and Internal Control Against Quality of Financial Statements - Latifah Yuniar; Nina Yamin; Jurana (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
This study aims to determine and analyze the influence of understanding of Government Accounting Standards (SAP) and Internal Control on the Quality of Financial Statements and their implications for accountability. The population in this study is all Regional Organization (OPD) Parigi Moutong District Government with deliberate sampling. PLS analysis is used to test both the measurement model and the structural model. The results showed that partially understanding of Government Accounting Standards and Internal Control had a positive and significant effect on the Quality of Financial Statements. While the Quality of Financial Reports also has a positive and significant effect on accountability. This shows that quality financial statements will have implications for the increasing accountability of an entity.